Microbiota in the honey bee gut and their association with bee health : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) in Ecology at Massey University School of Agriculture and Environment, Palmerston North, New Zealand - Taylor, Michelle (Massey University, 2020)
European honey bees (𝘈𝘱𝘪𝘴 𝘮𝘦𝘭𝘭𝘪𝘧𝘦𝘳𝘢) are the most prevalent bee species globally. Honey bees play a key role in human welfare as their pollination services support both the ecological viability of wild and native plants, and the economic viability of numerous nut, fruit, and vegetable crops. A decline in unmanaged pollinators in both natural and managed ecosystems, has resulted in an increased reliance on honey bees. Despite economic globalisation and increased demand for food over the past several decades contributing to an increase in the total number of honey bee colonies worldwide, annual colony mortality is high and has been attributed to seasonal conditions, poor management practice, outbreaks of pest and disease, pesticide poisoning, and the cost of management. It has been globally hypothesised that the cause of unexplained ‘rapid’ and ‘incremental’ colony loss, may result from interactions with bee pathogens (such as 𝘕𝘰𝘴𝘦𝘮𝘢 spp.), environmental factors and beekeeping management. The social and foraging behaviour of bees ensures that the gut, with its bacterial residents, is the conduit for assimilating of nutrients, antibiotics and oral poison, as well as the ingress and potential reservoir for gut pathogens. Characterisation of the bacterial community within the honey bee gut may provide further insight as to how these factors may affect bee health. New Zealand honey bees have been largely bred in isolation from the rest of the world, and thus potentially developed their own gut microbiome in response to factors specific to New Zealand. These include sources of native floral nectars (e.g. mānuka and rātā), the prohibition of antibiotics for disease management, and the absence of some global honey bee gut pathogens. My research is the 𝘧𝘪𝘳𝘴𝘵 to characterise the bacterial profiles and identify the relative abundance of core and less dominant bacteria in the gut of New Zealand honey bees. Diet and pathogens known to cause poor honey bee health were examined for their influence on gut bacteria. Bacterial phylotypes in the honey bee gut were identified by sequencing a fragment of the 16S rRNA gene. The problematic assignation of reliable taxonomic information for recently characterised honey bee gut bacteria was overcome by developing a customised 16S rRNA BLAST database that is compatible with QIIME2 sequencing software. This database has now been made available for other users. The five dominant core honey bee gut bacteria identified internationally were present in all apiaries/regions within New Zealand. Eight phylotypes were only identified in colonies deemed ‘sick’ by beekeepers. Three phylotypes may potentially be used as indicators of poor bee health: the family Rhizobiaceae, and the genera 𝘚𝘦𝘳𝘳𝘢𝘵𝘪𝘢 and 𝘈𝘤𝘦𝘵𝘰𝘣𝘢𝘤𝘵𝘦𝘳. Although each apiary was broadly similar in bacterial composition, the environmental conditions of each apiary appeared to influence the bacterial composition, in particular the available foraging sources. In contrast to international reports, the microsporidian gut pathogen 𝘕𝘰𝘴𝘦𝘮𝘢 𝘤𝘦𝘳𝘢𝘯𝘢𝘦 that shifted from the Asian honey bee 𝘈𝘱𝘪𝘴 𝘤𝘦𝘳𝘢𝘯𝘢𝘦 to the European honeybee in 2004 and was identified in New Zealand arond 2007, does not appear to have outcompeted 𝘕𝘰𝘴𝘦𝘮𝘢 𝘢𝘱𝘪𝘴. The latter was likely brought to New Zealand with the first bees in the 19th century. In my survey 𝘕. 𝘢𝘱𝘪𝘴 was identified in all sick apiaries whereas 𝘕. 𝘤𝘦𝘳𝘢𝘯𝘢𝘦 was only identified in one of the sick apiaries. Comparison of the gut bacteria in New Zealand bees with those from a pilot trial conducted in Connecticut, USA demonstrates that the dominant core bacteria are internationally widespread, and suggests that they have remained stable within an isolated population for over 60 years. This highlights the importance of the symbiotic relations that these gut bacteria have with honey bees. However, nine phylotypes were present only in the New Zealand samples, suggesting that some phylotypes may have adapted to New Zealand conditions or that dysbiosis may have occurred within New Zealand or elsewhere. This is the first example in the honey bee literature of DNA being analysed using different hypervariable regions. The variation between the number of amplicon sequence variants and their relative abundances highlight the importance of comparing data extracted using similar methodologies. I observed seasonal variation in the bacterial composition by examining five hives throughout a 12-month period. Gut bacteria in summer bees were the most diverse, autumn and winter bees had lesser diversity, and spring bees had the least diversity. This suggests that the increased bee population in spring may result in a cleansing of less prevalent bacteria for the year ahead. The relative abundance of 𝘎. 𝘢𝘱𝘪𝘤𝘰𝘭𝘢 and 𝘚. 𝘢𝘭𝘷𝘪 alter within individual bees throughout the year suggesting that these species may alter their abundance in response to occurrences within the gut and this may ultimately influence bee health and metabolism. The relative abundance of Rhizobiaceae peaked in winter when the bees live longer and often have elevated pathogen infections. The relative abundance of Rhizobiaceae exceeded that of all dominant core phylotypes, except 𝘓𝘢𝘤𝘵𝘰𝘣𝘢𝘤𝘪𝘭𝘭𝘶𝘴 spp. This supports my hypothesis that Rhizobiaceae may be a useful early indicator of poor bee health. Sucrose-rich diets, often fed to bees during periods of scarce food supply, were shown to increase the relative abundances of three less dominant core bacteria; Rhizobiaceae, Acetobacteraceae, and 𝘓𝘢𝘤𝘵𝘰𝘣𝘢𝘤𝘪𝘭𝘭𝘶𝘴 𝘬𝘶𝘯𝘬𝘦𝘦𝘪, and decreased the relative abundance of the core species 𝘍𝘳𝘪𝘴𝘤𝘩𝘦𝘭𝘭𝘢 𝘱𝘦𝘳𝘳𝘢𝘳𝘢. In combination, these diets significantly altered the bacterial composition. Acetogenic bacteria from the Rhizobiaceae and Acetobacteraceae families increased two- to five-fold when bees were fed sucrose, suggesting that sucrose fuels the proliferation of specific low-abundance primary sucrose-feeders. The gut pathogen 𝘕. 𝘢𝘱𝘪𝘴 did not appear to disrupt the development of 𝘎𝘪𝘭𝘭𝘪𝘢𝘮𝘦𝘭𝘭𝘢 𝘢𝘱𝘪𝘤𝘰𝘭𝘢, which normally forms the outer layer of the biofilm in the luminal surface of the honey bee ileum. A gut slurry inoculation from older worker bees increased abundance of bacterial phylotypes in newly emerged workers (NEWs), thus supporting the limited literature that NEWs acquire gut bacteria from worker bees. This study also confirms that NEWs are not axenic when they emerge from their cells as their guts contain low levels of 𝘎. 𝘢𝘱𝘪𝘤𝘰𝘭𝘢, 𝘚. 𝘢𝘭𝘷𝘪, 𝘓. 𝘢𝘱𝘪𝘴, 𝘓. 𝘮𝘦𝘭𝘭𝘪𝘴, 𝘓𝘢𝘤𝘵𝘰𝘣𝘢𝘤𝘪𝘭𝘭𝘶𝘴 𝘴𝘱𝘱., 𝘉𝘪𝘧𝘪𝘥𝘰𝘣𝘢𝘤𝘵𝘦𝘳𝘪𝘶𝘮 𝘴𝘱𝘱., 𝘚𝘦𝘳𝘳𝘢𝘵𝘪𝘢 spp., 𝘈𝘤𝘦𝘵𝘰𝘣𝘢𝘤𝘵𝘦𝘳 spp., Rhizobiaceae, and Cyanobacteria. Finally, this research also identified a correlation between the lack of abundant bacteria in the honey bee gut with an increase in the opportunistic colonising bacteria Rhizobiaceae and 𝘚𝘦𝘳𝘳𝘢𝘵𝘪𝘢. This is further evidence in support of my suggestion that the family Rhizobiaceae contains opportunistic bacteria and that the relative abundance of this family in honey bee guts may be a useful indicator of poor bee health. This work is thus the first study to examine gut bacteria in New Zealand honey bees and I have demonstrated that environmental factors and diet influence gut bacterial composition which may influence honey bee health and metabolism.
Keywords: Honeybee; Health; New Zealand; Gastrointestinal system; Microbiology; 310703 Microbial ecology